Traces of the oxygen isotope composition of ancient air in fossilized cosmic dust - Fabian Zahnow; Martin D. Suttle; Marina Lazarov; Stefan Weyer; Tommaso Di Rocco; Luigi Folco; Andreas Pack (Communications Earth & Environment)
Abstract As a sub-type of micrometeorites, I-type cosmic spherules form by complete melting and oxidation of extraterrestrial Fe, Ni metal particles during their atmospheric entry. All oxygen in the resulting Fe, Ni oxides sources from the Earth’s atmosphere and hence makes them probes for the composition of atmospheric oxygen. When recovered from sedimentary rocks, they allow the reconstruction of the triple oxygen isotope composition of past atmospheric O2, providing quantitative constraints on past CO2 levels or global primary production. Here we establish using fossil I-type cosmic spherules as an archive of Earth’s atmospheric composition with the potential for a unique record of paleo-atmospheric conditions dating back billions of years. We present combined triple oxygen and iron isotope compositions of a collection of fossil I-type cosmic spherules recovered from Phanerozoic sediments. We reconstruct the triple oxygen isotope anomalies of past atmospheric O2 and quantify moderate ancient CO2 levels during the Miocene (~8.5 million years) and late Cretaceous (~87 million years). We also demonstrate this method’s competitive precision for paleo-CO2 determination, despite challenges in finding micrometer-sized unaltered fossil I-type cosmic spherules. Our work indicates that morphologically intact spherules can be isotopically altered by terrestrial processes, underscoring the need for rigorous sample screening.